Answer
The solution to the equation is
![x=-1\pm\frac{i\sqrt[]{2}}{3}](https://img.qammunity.org/2023/formulas/mathematics/college/qvz5r34uc9wfwce2bqejjuwlv7a7i09lnk.png)
This can be written as
x = -1 ± 0.4714i
Or even be broken down further into
![\begin{gathered} x=-1+\frac{i\sqrt[]{2}}{3} \\ OR \\ x=-1-\frac{i\sqrt[]{2}}{3} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/9jqr8vvmemyubj30ggob4bkppwrpvo8l8n.png)
Step-by-step explanation
The quadratic formula can be used to solve all quadratic equations of the form
ax² + bx + c = 0
The quadratic formula is given as
![x=\frac{-b\pm\sqrt[]{b^2-4ac}}{2a}](https://img.qammunity.org/2023/formulas/mathematics/college/rxvf73usjbbwyik14knxdemoz21vfz2ufc.png)
For this question, we can write this given equation in the general form of a quadratic equation
9x² + 18x = -11
9x² + 18x + 11 = 0
Comparing this with ax² + bx + c = 0
a = 9
b = 18
c = 11
![\begin{gathered} x=\frac{-b\pm\sqrt[]{b^2-4ac}}{2a} \\ x=\frac{-18\pm\sqrt[]{18^2-4(9)(11)}}{2(9)} \\ x=\frac{-18\pm\sqrt[]{324-396}}{18} \\ x=\frac{-18\pm\sqrt[]{-72}}{18} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/y9a06gwmubrkhg8a3gyq6hycx8np0vhobk.png)
Noting that the square root of -1 is the complex number i
√(-72) = i√72
But,
√(72) = √(36×2) = √(36) × √(2) = 6√2
![\begin{gathered} x=\frac{-18\pm\sqrt[]{-72}}{18} \\ x=\frac{-18\pm i\sqrt[]{72}}{18} \\ x=\frac{-18\pm6i\sqrt[]{2}}{18} \\ x=(-18)/(18)\pm\frac{6i\sqrt[]{2}}{18} \\ x=-1\pm\frac{i\sqrt[]{2}}{3} \\ x=1+\frac{i\sqrt[]{2}}{3} \\ OR \\ x=-1-\frac{i\sqrt[]{2}}{3} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/uibcso3czj6w5454cchin642dk1s3y9t0d.png)
Hope this Helps!!!